Gestão do conhecimento: uma análise do setor automobilístico a partir de fatores contextuais da organização - Gonzalez, Rodrigo Valio Dominguez (2011)
The latest models on Knowledge Management (KM) recognize four stages to their practice: acquisition, storage, distribution and use of knowledge that presents itself as tacit and explicit. The KM is characterized as a multidisciplinary discipline, involving aspects of technical and social order and due to the diversity of issues about this topic, it is essential to delimit their study. In this sense, the proposed delimitation for this research is social and coordination, involving the identification of contextual factors, developed internally in organizations that support the process of KM in automotive companies. These contextual factors are defined based on organizational aspects to enable the development of the four phases of the KM, especially the development of human resources, organizational culture, teamwork, organizational structure and the way how knowledge is developed and absorbed internally. This thesis also identifies groupings (clusters) composed of companies with similar characteristics as the development of these contextual factors, analyzing the implications of the clusters features for KM and for the use of knowledge. The automotive companies can be characterized as advanced for improvement and innovation processes, and thus the knowledge management is fundamental to the sustainability of these activities. To achieve this goal, this research uses a quantitative research method, based on a survey. Data analysis is performed using multivariate statistical techniques of factor analysis, cluster analysis and discriminant analysis. In regarding the results were collected eight contextual factors that support the process of GC, and also identified four clusters for the development of these factors: innovate, exploited, exploited and Laggards. The companies of the first two groups have a better capacity to absorb knowledge and build a broader base of primary knowledge, making them more innovative, and the other two groups take a more reactive posture within the industry, following the development proposed by the companies of first two clusters. In the latter two groups, in particular exploited, there is the development of factors related to incremental improvement and teamwork, showing a tendency to use the knowledge designed to improve production efficiency.